PROFIL KROMATOGRAFI LAPIS TIPIS MINYAK ATSIRI SEREH (Cymbopogon citratus) - Rani Prabandari (Viva Medika, 2017)
Abstract. Rhodinol has been isolated from citronella oil. Isolation of lemongrass oil is done by using the distillation method. Samples used were citronella harvested for 6 months and 9 months. Silent phase used TLC plate slika gel F254 with a size of 2 x 10 cm and the mobile phase used was Toluen: Ethyl Acetate (93: 7). Results of Thin Layer Chromatography HRF profile obtained for experiment I (citronella harvesting age 6 months) 32, 77, 87 and Experiment II (lemongrass harvest age 9 months) respectively 25, 73, 81.